Implementasi Manajemen Media Kartu Huruf Dalam Pembelajaran Untuk Meningkatkan Kemampuan Baca Tulis Huruf Al-Qur’an - Andri Marta Sudirja (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this research is to gain an overview of media management implementations letter card hijaiyah to foster literacy at grade Qur'an 2 MI Cibeusi Jatinangor of Sumedang District. This study used a qualitative research with descriptive approach. The technique of collecting data through observation, interviews and documentation study. The results of this study indicate that the implementation management of the letters card in the learning begins with a lesson plan, which is making lesson plan or RPP made by each teacher at the beginning of the semester. Evaluation of learning is done by assessment of student learning outcomes. Interest teachers assess student learning outcomes is to measure student success, measure students' abilities, and material evaluation of the learning process. Supportingfactors the implementation of media management hijaiyah letter card are as follows: Teachers occupy an important role as a source of learning, the use of media letter card is preferred by students in grade 2 MI Cibeusi, enthusiastic students in learning BTAQ very high if there is a medium of learning, while the inhibiting factor is the limited number of letters media card, so the learning environment becomes inconducive.